Hypofractionated radiotherapy in the real-world setting: An international ESTRO-GIRO survey. (April 2021) - Rodin, Danielle; Tawk, Bouchra; Mohamad, Osama; Grover, Surbhi; Moraes, Fabio Y.; Yap, Mei Ling; Zubizarreta, Eduardo; Lievens, Yolande
Highlights: Conventional and hypofractionated radiotherapy are equivalent in many disease sites. Less hypofractionation in low- and lower-middle income countries and Asia-Pacific. Lack of long-term data, inferior local control, and toxicity cited as barriers. Significant global variation in use of hypofractionation for curative indications. Accepted for palliation of breast, prostate, cervical cancer, and bone metastases. Abstract: Background and purpose: Multiple large trials have established the non-inferiority of hypofractionated radiotherapy compared to conventional fractionation. This study will determine real-world hypofractionation adoption across different geographic regions for breast, prostate, cervical cancer, and bone metastases, and identify barriers and facilitators to its use. Materials and methods: An anonymous, electronic survey was distributed from January 2018 through January 2019 to radiation oncologists through the ESTRO-GIRO initiative. Predictors of hypofractionation were identified in univariable and multivariable regression analyses. Results: 2316 radiation oncologists responded. Hypofractionation was preferred in node-negative breast cancer following lumpectomy (82·2% vs. 46·7% for node-positive; p  < 0.001), and in low- and intermediate-risk prostate cancer (57·5% and 54·5%, respectively, versus 41·2% for high-risk ( p  < 0.001)). Hypofractionation was used in 32·3% of cervix cases in Africa, but <10% in other regions ( p  < 0.001). For palliative indications, hypofractionation was preferred by the majority of respondents. Lack of long-term data and concerns about local control and toxicity were the most commonly cited barriers. In adjusted analyses, hypofractionation was least common for curative indications amongst low- and lower-middle-income countries, Asia-Pacific, female respondents, small catchment areas, and in centres without access to intensity modulated radiotherapy. Conclusion: Significant variation was observed in hypofractionation across curative indications and between regions, with greater concordance in palliation. Using inadequate fractionation schedules may impede the delivery of affordable and accessible radiotherapy. Greater regionally-targeted and disease-specific education on evidence-based fractionation schedules is needed to improve utilization, along with best-case examples addressing practice barriers and supporting policy reform.